Design and Analysis of Fractional-order Oscillators Using Scilab - Bingi, K. (Institute of Electrical and Electronics Engineers Inc., 2019)
Over the years the chaotic behavior of fractional-order oscillators has been utilized in many real-world applications. In all the developments, the implementation and evaluation of these oscillators are done using MATLAB software. However, MATLAB is very expensive even for a limited number of licenses. Hence, a major alternative and open-source software i.e., Scilab can be used for these numerical computations. Therefore, in this paper, the fractional-order Van der Pol and Duffing oscillators are developed and analyzed using Scilab for various commensurate and non-commensurate orders. The simulation study shows that the fractional-order oscillators can be effectively implemented and analyzed using Scilab, Â© 2019 IEEE.